All-solid-state battery containing bipositive sulfide electrolyte

By using sulfide electrolytes containing double positive ions in all-solid state batteries, the complex problems of lithium dendrites' growth and preparation processes are solved, and the battery life is extended and production costs are reduced.

CN119518078APending Publication Date: 2025-02-25QINGYUAN HUATUO ENERGY CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411752853.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing all-solid state batteries have problems with lithium dendrites, resulting in limited battery life and safety, and complex preparation process, high cost, and unstable batch quality.

Method used

Li5.5-xAgxS4.5PCl1.5 or Li5.3-xAgxS4.3PClBr0.7 is prepared by raw materials such as silver sulfide, lithium sulfide, diphosphate pentasulfide, anhydrous lithium chloride or silver chloride. New type of solid electrolyte simplifies the preparation process of solid electrolyte in battery and reduces production costs.

Benefits of technology

It reduces the growth and puncture of lithium dendrites, improves the circulation life of all solid-state batteries, simplifies the preparation process, reduces production costs, and improves the stability of batch quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518078A_ABST
    Figure CN119518078A_ABST
Patent Text Reader

Abstract

According to the all-solid-state battery, argyrodite type electrolytes Li < 5.5-x > Ag < x > S < 4.5 > PCl < 1.5 > and Li < 5.3-x > Ag < x > S < 4.3 > PCl < Br < 0.7 > are prepared by using silver sulfide, cuprous sulfide, lithium sulfide, phosphorus pentasulfide, anhydrous lithium chloride or silver chloride, phosphorus pentasulfide and anhydrous lithium chloride as raw materials. The all-solid-state battery is not limited to solid-state electrolytes Li < 5.5-x > Ag < x > S < 4.5 > PCl < 1.5 >; on a single parent Li6PS5Cl, Li5.3 PS4.3 Cl < 1.7 >, Li5.4 PS4.4 Cl < 1.6 >, Li5.5 PS4.5 Cl < 1.5 >, Li5.7 PS4.7 Cl < 1.3 >, Li5.25 PS4.25 Cl < 17 >, Li5.2 PS4.2 Cl < 1.8 > and the like, multiple halogen element anions are used for replacing single halide anions, and silver ions Ag < + > or cuprous ions Cu < + > are used for partially replacing lithium ions, so that the solid electrolyte with the same order of magnitude as that of the single parent in ion conductivity is obtained, and the prepared electrolyte membrane has the cascade heterogeneous interface gating characteristic and can be applied to the field of lithium ion batteries, lithium ion batteries, lithium ion batteries, lithium ion batteries, lithium ion batteries, lithium ion batteries, lithium ion batteries, lithium ion batteries, lithium ion batteries and lithium ion batteries. The transmission movement of lithium ions in an electric field can be adjusted, anisotropic growth of lithium dendrites is reduced, the service life of the all-solid-state battery is greatly prolonged, meanwhile, raw materials with lower manufacturing cost are adopted, the preparation process of the solid-state battery is simplified, the production cost is greatly reduced, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of all-solid-state batteries, and in particular to an all-solid-state battery containing a sulfide electrolyte containing double positive ions. Background Art

[0002] In recent years, all-solid-state batteries have attracted widespread attention due to their high energy density and safety. However, all-solid-state batteries in the existing technology still have some key problems, such as the growth of lithium dendrites, which limits the life and safety of the battery. In 2020, the Samsung Research Institute team in South Korea designed and developed a unique silver-carbon (Ag-C) composite anode to replace the lithium (Li) metal anode, and combined with argyrodite-type solid electrolytes to prepare a multi-ampere-hour soft-pack all-solid-state battery, achieving an energy density of up to 942Wh / kg, and being able to maintain a stable cycle for more than 1,000 times, which has broad application prospects in high-energy-density applications such as electric vehicles and energy storage. The preparation of this all-solid-state battery has the disadvantages of expensive process equipment, lengthy and complicated battery preparation process, expensive nanosilver particle materials, uneven size and distribution of nanosilver particles, anisotropy when combined with lithium in the solid-state battery layer, and easy growth of lithium dendrites that pierce the electrolyte layer after multiple cycles, resulting in unstable batch quality of all-solid-state batteries. Summary of the invention

[0003] An object of the present invention is to provide an all-solid-state battery containing a sulfide electrolyte containing double positive ions.

[0004] An all-solid-state battery containing a sulfide electrolyte with double positive ions according to an embodiment of the present invention comprises the following steps:

[0005] S1. preparing a sulfide solid electrolyte;

[0006] S2. Make and test all-solid-state batteries.

[0007] Optionally, the preparation of the sulfide solid electrolyte specifically includes:

[0008] In an argon dry atmosphere, silver sulfide, Li2S, P2S5, LiBr and LiCl with a purity of more than 99% are weighed according to a specific molar ratio and placed in a ball mill, and the premixed raw material is placed in a 500ml steel ball mill, the ball-to-material weight ratio in the steel ball mill is 5:1, and the flat bottom cover is screwed and sealed, the ball mill is sealed, and high-energy ball milling is performed at a speed of 500rpm for 20h, during which the tank body is turned over;

[0009] In an argon dry atmosphere, the mixed dry powder is pressed into a block material, which is placed in an argon dry atmosphere and loaded into a quartz ceramic container. The block material is then taken out of the inert glove box and placed in an extremely fast heating electric furnace for heating for 1-10 minutes. The power supply is turned off, and after cooling to room temperature, it is transferred to an inert glove box in an argon dry atmosphere for grinding and crushing to obtain a sulfide solid electrolyte.

[0010] Optionally, the argon drying atmosphere is an environment with a moisture content of less than 1 ppm and an oxygen content of less than 1 pmm.

[0011] Optionally, the sulfide solid electrolyte is in Li 5.3 S 4.3 PClBr 0.7 、Li6PS5Cl,Li 5.3 PS 4.3 Cl 1.7 , Li 5.4 PS 4.4 Cl 1.6 , Li 5.5 PS 4.5 Cl 1.5 , Li 5.7 PS 4.7 Cl 1.3 , Li 5.25 PS 4.25 Cl 17 , Li 5.2 PS 4.2 Cl 1.8 On a single matrix structure, a single halogen anion is replaced by a variety of halogen element anions, and lithium ions are partially replaced by silver ions Ag+ and cuprous ions Cu+, to obtain a solid electrolyte with higher conductivity than that of a single matrix. The prepared electrolyte membrane has cascade heterogeneous interface gating characteristics, which regulates the transmission movement of lithium ions under an electric field.

[0012] Optionally, a LZO coating solution is prepared from anhydrous 2-propanol, a methanol solution in 10% methanol solution, and zirconium tetrapropoxide in a molar ratio of 200:20:1, and NMC is dispersed in the above solution and stirred for 1 hour; subsequently, the propanol is evaporated in a vacuum water bath at 50°C and continuously ultrasonicated to prevent NMC particle aggregation. After shedding, the precursor is heated at 300°C in the presence of air for 1 hour to obtain LZO-coated NMC.

[0013] Optionally, by mixing LiBO2-coated NMC, Li 5.5 S 4.5 PCl 1.5A composite positive electrode was prepared with sulfide electrolyte particles, carbon nanofibers and polytetrafluoroethylene binder PTFE in a weight ratio of 85:15:3:1.5. Submicron-sized SSE particles were used to increase the contact area and cathode density. The positive electrode sheet was prepared by a dry process. The thickness of the positive electrode sheet was about 100 μm, and the variable thickness range was 30 to 250 μm. All processes were carried out in an argon glove box or a drying room.

[0014] Optionally, a carbon-coated lithium stainless steel foil negative electrode is prepared by preparing stainless steel foil and carbon black powder as anode active materials, mixing the carbon black powder in N-methylpyrrolidone containing 7wt% polyvinylidene fluoride, slowly adding N-methylpyrrolidone to the mixture under constant stirring, using a mixer to prepare a negative electrode slurry, using a screen printer to coat the slurry on a 10μm thick stainless steel foil, and further drying the obtained electrode under vacuum at 100°C for 12h. The thickness of the carbon coating layer is 5-10μm, and then a thin metal lithium strip is attached and slightly heated to obtain a carbon-coated lithium stainless steel foil negative electrode, or tetrahydrofuran-containing lithium powder is dripped on the carbon-coated stainless steel foil, and the tetrahydrofuran is dried to obtain a carbon-coated lithium stainless steel foil negative electrode.

[0015] Optionally, a double-layer solid electrolyte layer SSE is prepared, and the prepared Li 5.5 S 4.5 PCl 1.5 The solid electrolyte layer is mixed with 1% PTFE as a binder. The electrolyte layer is prepared by a PTFE dry method. The sulfide electrolyte powder containing double positive ions is mixed with 1% PTFE as a binder. After being evenly dispersed by ultra-high-speed air flow shearing, it is hot rolled twice to obtain a double-layer self-supporting electrolyte membrane with a thickness ranging from 25 to 90 μm.

[0016] Optionally, mix LiBO2 coated NMC, Li 5.5 S 4.5 PCl 1.5 Sulfide electrolyte particles, carbon nanofibers and polytetrafluoroethylene binder, the prepared composite positive electrode is placed on the top, Li 5.5 S 4.5 PCl 1.5 A solid electrolyte layer mixed with 1% PTFE binder is placed on top, and a sulfide electrolyte membrane containing double positive ions is placed on the surface of carbon-coated lithium steel foil. Heat-resistant Teflon membranes are used at both ends of the battery cell. A hot press is used to bond the electrode membrane and the current collector under pressure to achieve bonding and curing, and a compacted battery cell with a dense porosity of <3% is obtained.

[0017] Optionally, the anode, cathode and solid electrolyte sheets are prepared according to the size requirements, all the electrodes and electrolyte sheets are stacked and packed into a laminated bag, the laminated bag is vacuum treated, sealed, and the battery is pressurized at 490MPa by a static press, after pressing, the battery is taken out of the laminated bag, and the Al and Ni terminals of the cathode and anode are welded respectively using an ultrasonic welder, the battery is placed in a laminated bag and vacuum sealed again. Most of the assembly processes are carried out in a dry air atmosphere, where the dew point is controlled below -50°C.

[0018] The beneficial effects of the present invention are:

[0019] The present invention uses silver sulfide, lithium sulfide, phosphorus pentasulfide, anhydrous lithium chloride or silver chloride, lithium sulfide, phosphorus pentasulfide, anhydrous lithium chloride as raw materials to prepare a novel argyrodite-type solid electrolyte Li 5.5-x Ag x S 4.5 PCl 1.5 , or Li 5.3-x Ag x S 4.3 PClBr 0.7 The electrolyte has dual positive ion transmission performance. When the positive electrode is de-lithiumized, it stabilizes the formation of a thin lithium metal layer at the negative terminal, forming a lithium-silver low-temperature eutectic in the all-solid-state battery, etc., reducing the anisotropic growth of lithium dendrites in the electrochemical cycle. The degree of electrolyte puncture caused by the growth of lithium dendrites will be reduced; when the positive electrode is embedded with lithium ions, the lithium ions are removed from the lithium-silver low-temperature eutectic at the negative terminal, etc., and the residual silver-carbon pore structure still has good electrical network conductivity. Silver ions will have a viscous effect on the transmission of lithium ions with faster movement speeds. Silver ions will supplement the vacancies after lithium ion transition to a certain extent, delay the aggregation of lithium ions, prevent the growth of lithium dendrites, and puncture the electrolyte layer. Used in all-solid-state batteries, it simplifies the preparation process of battery solid electrolytes, greatly reduces production costs, improves production efficiency, and can greatly increase the cycle life of all-solid-state batteries. Or cuprous sulfide is used instead of silver sulfide, which can reduce the cost of solid-state batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0021] Figure 1 A structural diagram of an all-solid-state battery containing a sulfide electrolyte with double positive ions proposed by the present invention;

[0022] Figure 2 A line graph showing that the electrochemical cycle life of an all-solid-state battery containing a sulfide electrolyte with double positive ions at 25 degrees Celsius is stable > 600 times;

[0023] Figure 3 This is an impedance test diagram of a double positive ion sulfide electrolyte (containing bromine) of an all-solid-state battery containing a double positive ion sulfide electrolyte proposed by the present invention, and the conductivity is 4.2mS / cm;

[0024] Figure 4 This is a diagram verifying the effect of an all-solid-state battery containing a sulfide electrolyte containing double positive ions proposed in the present invention. DETAILED DESCRIPTION

[0025] The present invention will now be described in further detail with reference to the accompanying drawings. These drawings are simplified schematic diagrams, which only illustrate the basic structure of the present invention in a schematic manner, and therefore only show the components related to the present invention.

[0026] refer to Figure 1-4 , an all-solid-state battery containing a sulfide electrolyte with double positive ions, comprising the following steps:

[0027] S1. preparing a sulfide solid electrolyte;

[0028] S2. Make and test all-solid-state batteries.

[0029] In this embodiment, the preparation of the sulfide solid glass ceramic melt

[0030] In an argon dry atmosphere (moisture content less than 1ppm, oxygen content less than 1pmm), silver sulfide, Li2S, P2S5, LiBr and LiCl with a purity of more than 99% are weighed according to a specific molar ratio and placed in a ball mill. The premixed raw material is placed in a 500ml steel ball mill (ball-to-material weight ratio is 5:1), and the flat bottom cover is screwed and sealed. The ball mill is sealed and high-energy ball milling is performed at a speed of 500rpm for 20 hours, during which the tank body is turned over.

[0031] In an argon dry atmosphere (moisture content less than 1ppm, oxygen content less than 1pmm), the mixed dry powder is pressed into a block material. The block material is placed in an argon dry atmosphere (moisture content less than 1ppm, oxygen content less than 1pmm) and loaded into a quartz ceramic container. Then take out the inert glove box, put it in an extremely fast heating electric furnace, heat it at a high power setting for several minutes or tens of minutes, turn off the power supply, cool to room temperature, and then transfer it to an inert glove box argon dry atmosphere for grinding and crushing to obtain the sulfide solid electrolyte of this embodiment.

[0032] The present invention is not limited to solid electrolyte Li 5.5-x Ag x S 4.5 PCl 1.5 , or Li 5.3-x Ag x S4.3 PClBr 0.7 .

[0033] In Li 5.3-x S 4.3 PClBr 0.7 、Li6PS5Cl,Li 5.3 PS 4.3 Cl 1.7 , Li 5.4 PS 4.4 Cl 1.6 , Li 5.5 PS 4.5 Cl 1.5 , Li 5.7 PS 4.7 Cl 1.3 , Li 5.25 PS 4.25 Cl 17 , Li 5.2 PS 4.2 Cl 1.8 On a single matrix structure, a single halogen anion is replaced by a variety of halogen element anions, and lithium ions are partially replaced by silver ions Ag+ or cuprous ions Cu+, so as to obtain a solid electrolyte with the same order of magnitude of ion conductivity as the single matrix. The prepared electrolyte membrane has cascade heterogeneous interface gating characteristics, which regulates the transmission movement of lithium ions under an electric field.

[0034] Make all-solid-state batteries according to the above structural diagram and test them

[0035] Preparation of nanolayers on the surface of positive electrode particles coated with NCM oxides, etc.

[0036] LiBO2-coated NMC was prepared using H3BO3.

[0037] H3BO3 and NMC were dry mixed and stirred for 1 h; subsequently, the precursor was heated at 300 °C in the presence of argon for 1 h to obtain LiBO2-coated NMC.

[0038] Alternatively, LZO coating solution was prepared from anhydrous 2-propanol, lithium methoxide (10% methanol solution in methanol) and zirconium (IV) tetrapropoxide in a molar ratio of 200:20:1. NMC was dispersed in the above solution and stirred for 1 h; subsequently, propanol was evaporated in a vacuum water bath at 50 °C and continuously sonicated to prevent NMC particle aggregation. After exfoliation, the precursor was heated at 300 °C in the presence of air for 1 h to obtain LZO-coated NMC.

[0039] By mixing LiBO2-coated NMC, Li 5.5 S 4.5 PCl 1.5The composite positive electrode was prepared by mixing sulfide electrolyte particles, carbon nanofibers and polytetrafluoroethylene binder (85:15:3:1.5 by weight). Submicron-sized SSE particles were used to increase the contact area and cathode density. The positive electrode sheet was prepared by a dry process. The thickness of the positive electrode sheet is about 100μm, and the variable thickness range is 30 to 250μm. The uniformity of the electrode sheet may be due to different processing parameters, and there may be poor conductivity of the electrical interconnection network or poor preparation of active particles, conductive agent distribution, and dense porosity <3%. All processes were carried out in an argon glove box or a dry room (dew point below -50°C).

[0040] Preparation of carbon-coated lithium stainless steel foil negative electrode. Stainless steel foil and carbon black powder were prepared as anode active materials. The carbon black powder was mixed in N-methylpyrrolidone containing 7wt% polyvinylidene fluoride. N-methylpyrrolidone was slowly added to the mixture under constant stirring, and a negative electrode slurry was prepared using a mixer. The slurry was then coated on a 10μm thick stainless steel foil using a screen printer, and the obtained electrode was further dried at 100°C under vacuum for 12h. The thickness of the carbon coating layer is 5-10μm, and then a thin metal lithium strip is attached and slightly heated to form a carbon-coated lithium stainless steel foil negative electrode, or tetrahydrofuran containing lithium powder is dripped on the carbon-coated stainless steel foil, and the tetrahydrofuran is dried to obtain a carbon-coated lithium stainless steel foil negative electrode.

[0041] Preparation of double-layer solid electrolyte layer SSE. Prepared Li 5.5 S 4.5 PCl 1.5 The solid electrolyte layer is mixed with 1% PTFE as a binder. The electrolyte layer is prepared by a PTFE (polytetrafluoroethylene) dry method, and the sulfide electrolyte powder containing double positive ions prepared by the present invention is mixed with 1% PTFE as a binder, and after being uniformly dispersed by ultra-high-speed air flow shearing, hot rolling is performed twice to obtain a double-layer self-supporting electrolyte membrane with a thickness ranging from 25 to 90 μm.

[0042] Hybrid LiBO2-coated NMC, Li 5.5 S 4.5 PCl 1.5 The composite cathode prepared by sulfide electrolyte particles, carbon nanofibers and polytetrafluoroethylene binder (85:15:3:1.5 by weight) was placed on the top, and Li 5.5 S 4.5 PCl 1.5 A solid electrolyte layer mixed with 1% PTFE as a binder is placed on top, and a sulfide electrolyte membrane containing double positive ions is placed on the surface of a carbon-coated lithium (10 μm thick) steel foil. Heat-resistant Teflon membranes are used at both ends of the battery cell, and a hot press is used to bond the electrode membrane and the current collector under pressure to achieve bonding and curing, thereby obtaining a compacted battery cell with a dense porosity of <3%.

[0043] A puncher is used to cut electrode sheets of the required button battery size to make a 2016 shell button type all-solid-state battery, and the inventory, electrochemical cycle life, performance in a high-temperature oil bath and other parameters of the 2016 shell button type all-solid-state battery are tested. The test results show that the all-solid-state battery made of the sulfide electrolyte containing double positive ions of the present invention has many advantages such as high energy density, long cycle life, and high temperature resistance.

[0044] Manufacturing of soft-pack battery pouch-type full cells. The anode, cathode and solid electrolyte sheets are prepared according to the size requirements, and all electrodes and electrolyte sheets are stacked and packaged into laminated bags. After the laminated bag is vacuum-treated, it is sealed and the battery is pressurized at 490MPa by an isostatic press. After pressing, the battery is taken out of the laminated bag, and the Al and Ni terminals of the cathode and anode are welded using an ultrasonic welder, respectively. The battery is then loaded into a laminated bag and vacuum-sealed again. Most of the assembly process is carried out in a dry air atmosphere, where the dew point is controlled below -50°C.

[0045] The obtained Li 5.5-x Ag x S 4.5 PCl 1.5 , the conductivity of the cold pressed block at 19°C was >7mS / cm. The sample temperature was increased and the bulk impedance was measured at high frequency through the real axis. The Li 5.5-x Ag x S 4.5 PCl 1.5 , at 60℃, the real impedance value of the cold pressed block is 9.55 ohms, and the conductivity test is >10mS / cm,

[0046] This patent application uses cheaper Ag2S powder instead of expensive nano silver powder, which can significantly reduce the cost of producing solid electrolytes. After mixing with other materials, crushing, and then placing in a quartz container, and heating in an electric furnace, an electrolyte product containing two positive ions is obtained.

[0047] Li 5.3-x Ag x S 4.3 PClBr 0.7 With the parent electrolyte Li 5.3 S 4.3 PClBr 0.7 Compared with the ion conductivity of 10mS / cm, the real impedance value becomes a little larger, and the ion conductivity is about 4.0mS / cm.

[0048] Experimental measurements show that the electrolyte with this composition not only has high ion conductivity, but also the prepared PTFE dry electrolyte membrane has excellent toughness, and the occurrence of cracks in the PTFE dry electrolyte membrane is drastically reduced.

[0049] Applied in all-solid-state batteries, such as Figure 1 As shown, the electrolyte can simultaneously transport lithium ions and silver ions when there is an external voltage, and the silver ions will have a viscosity phenomenon on the faster moving lithium ion transmission. The electrolyte has dual positive ion transmission performance. When the positive electrode de-lithium ions, the formation of a thin lithium metal layer at the negative end is stabilized to form a lithium-silver low-temperature eutectic in the all-solid-state battery. Compared with Samsung's use of nano-silver particles at the negative end, lithium nucleates on the nano-silver particles, and the degree of electrolyte puncture caused by the growth of lithium dendrites will be reduced. When the positive electrode is embedded with lithium ions, the lithium ions escape from the negative end lithium-silver low-temperature eutectic, etc., and the residual silver-carbon pore structure still has good electrical network conductivity. Silver ions will have a viscosity effect on the faster moving lithium ion transmission. Silver ions will supplement the vacancies after lithium ion transition to a certain extent, delay the aggregation of lithium ions, prevent the growth of lithium dendrites, puncture the electrolyte layer, etc., thereby improving the cycle life of the all-solid-state battery.

[0050] The present implementation method has cheap raw materials and can manufacture high-conductivity sulfide electrolytes for double (lithium silver) cation transport on an industrial scale. The transmission performance of lithium silver ions in a voltage field is tested by an impedance meter, etc. The cold-pressed powder conductivity is >7ms / cm, and it is experimentally verified that the growth degree of lithium dendrites can be reduced, the probability of puncturing the electrolyte layer, etc. can be greatly reduced, the process steps can be simplified, and the preparation of all-solid-state batteries has a longer cycle life and stable battery batch quality.

[0051] The present invention uses silver sulfide, lithium sulfide, phosphorus pentasulfide, anhydrous lithium chloride or silver chloride, lithium sulfide, phosphorus pentasulfide, anhydrous lithium chloride as raw materials to prepare a novel argyrodite-type solid electrolyte Li 5.5-x Ag x S 4.5 PCl 1.5 , or Li 5.3-x Ag x S 4.3 PClBr 0.7 The electrolyte has dual positive ion transmission performance. When the positive electrode is stripped of lithium ions, it stabilizes the formation of a thin lithium metal layer at the negative end, forming a lithium-silver low-temperature eutectic in the all-solid-state battery, etc., reducing the anisotropic growth of lithium dendrites in the electrochemical cycle. The degree of electrolyte puncture caused by the growth of lithium dendrites will be reduced; when the positive electrode is embedded with lithium ions, the lithium ions are removed from the lithium-silver low-temperature eutectic at the negative end, etc., and the residual silver-carbon pore structure still has good electrical network conductivity. Silver ions will have a viscous effect on the transmission of lithium ions with faster movement speeds. Silver ions will supplement the vacancies after lithium ion transition to a certain extent, delay the aggregation of lithium ions, prevent the growth of lithium dendrites, and puncture the electrolyte layer. Used in all-solid-state batteries, it simplifies the preparation process of battery solid electrolytes, greatly reduces production costs, improves production efficiency, and can greatly increase the cycle life of all-solid-state batteries.

[0052] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. An all-solid-state battery containing a sulfide electrolyte containing a double positive ion, characterized in that: The steps include: S1. preparing a sulfide solid electrolyte; S2. Make and test all-solid-state batteries.

2. The all-solid-state battery containing a sulfide electrolyte containing double positive ions according to claim 1, characterized in that: The preparation of the sulfide solid electrolyte specifically includes: In an argon dry atmosphere, silver sulfide, Li2S, P2S5, LiBr and LiCl with a purity of more than 99% are weighed according to a specific molar ratio and placed in a ball mill, and the premixed raw material is placed in a 500ml steel ball mill, the ball-to-material weight ratio in the steel ball mill is 5:1, and the flat bottom cover is screwed and sealed, the ball mill is sealed, and high-energy ball milling is performed at a speed of 500rpm for 20h, during which the tank body is turned over; In an argon dry atmosphere, the mixed dry powder is pressed into a block material, which is placed in an argon dry atmosphere and loaded into a quartz ceramic container. The block material is then taken out of the inert glove box and placed in an extremely fast heating electric furnace for heating for 1-10 minutes. The power supply is turned off, and after cooling to room temperature, it is transferred to an inert glove box in an argon dry atmosphere for grinding and crushing to obtain a sulfide solid electrolyte.

3. The all-solid-state battery containing a sulfide electrolyte containing double positive ions according to claim 2, characterized in that: The argon dry atmosphere is an environment with a moisture content of less than 1 ppm and an oxygen content of less than 1 pmm.

4. The all-solid-state battery containing a sulfide electrolyte with double positive ions according to claim 2, characterized in that: The sulfide solid electrolyte is 5.3 S 4.3 PClBr 0.7 ,Li6PS5Cl,Li 5.3 PS 4.3 Cl 1.7 , Li 5.4 PS 4.4 Cl 1.6 , Li 5.5 PS 4.5 Cl 1.5 , Li 5.7 PS 4.7 Cl 1.3 , Li 5.25 PS 4.25 Cl 17 , Li 5.2 PS 4.2 Cl 1.8 On a single matrix structure, a single halogen anion is replaced by a variety of halogen element anions, and lithium ions are partially replaced by silver ions Ag+ or cuprous ions Cu+, to obtain a solid electrolyte with the same order of magnitude of ion conductivity as the single matrix. The prepared electrolyte membrane has cascade heterogeneous interface gating characteristics, which regulates the transmission movement of lithium ions under an electric field.

5. According to claim 1, the all-solid-state battery containing a sulfide electrolyte with double positive ions, wherein the positive electrode powder is characterized in that the surface has a complete nano-coating layer, not limited to LiBO2, Li2ZrO3 coating, coated NMC.

6. The all-solid-state battery containing a sulfide electrolyte with double positive ions according to claim 5, characterized in that: By mixing LiBO2-coated NMC, Li 5.5 S 4.5 PCl 1.5 A composite positive electrode was prepared with sulfide electrolyte particles, carbon nanofibers and polytetrafluoroethylene binder PTFE in a weight ratio of 85:15:3:1.

5. Submicron-sized SSE particles were used to increase the contact area and cathode density. The positive electrode sheet was prepared by a dry process. The thickness of the positive electrode sheet was about 100 μm, and the variable thickness range was 30 to 250 μm. All processes were carried out in an argon glove box or a drying room.

7. The all-solid-state battery containing a sulfide electrolyte with double positive ions according to claim 6, characterized in that: Preparation of carbon-coated lithium stainless steel foil negative electrode, prepare stainless steel foil and carbon black powder as anode active materials, mix carbon black powder in N-methylpyrrolidone containing 7wt% polyvinylidene fluoride, slowly add N-methylpyrrolidone to the mixture under constant stirring, use a mixer to prepare negative electrode slurry, use a screen printer to coat the slurry on a 10μm thick stainless steel foil, further dry the obtained electrode under vacuum at 100°C for 12h, the thickness of the carbon coating layer is 5-10μm, then adhere a thin metal lithium strip and slightly heat it to obtain a carbon-coated lithium stainless steel foil negative electrode, or drip tetrahydrofuran containing lithium powder on the carbon-coated stainless steel foil, and dry the tetrahydrofuran to obtain a carbon-coated lithium stainless steel foil negative electrode.

8. The all-solid-state battery containing a sulfide electrolyte with double positive ions according to claim 7, characterized in that: Preparation of double-layer solid electrolyte layer SSE, preparation of Li 5.5 S 4.5 PCl 1.5 The solid electrolyte layer is mixed with 1% PTFE as a binder. The electrolyte layer is prepared by a PTFE dry method. The sulfide electrolyte powder containing double positive ions is mixed with 1% PTFE as a binder. After being evenly dispersed by ultra-high-speed air flow shearing, it is hot rolled twice to obtain a double-layer self-supporting electrolyte membrane with a thickness ranging from 25 to 90 μm.

9. The all-solid-state battery containing a sulfide electrolyte with double positive ions according to claim 8, characterized in that: LiBO2 coated NMC and Li were mixed at a weight ratio of 85:15:3:1.

5. 5.5 S 4.5 PCl 1.5 Sulfide electrolyte particles, carbon nanofibers and polytetrafluoroethylene binder PTFE, the prepared composite positive electrode is placed on the top, Li 5.5 S 4.5 PCl 1.5 A solid electrolyte layer mixed with 1% PTFE as a binder is placed on top, and a sulfide electrolyte membrane containing double positive ions is placed on the surface of the carbon-coated lithium steel foil. Heat-resistant Teflon membranes are used at both ends of the battery cell and are bonded under pressure using a hot press to achieve bonding and curing of the electrode membrane and the current collector to obtain a compacted battery cell with a dense porosity of <3%.

10. The all-solid-state battery containing a sulfide electrolyte with double positive ions according to claim 9 is not limited to soft-package aluminum-plastic film packaging, but covers stainless steel button batteries, other rigid non-deformable metal shells (with insulating paint, etc.) packaging, etc. The soft-package packaging is characterized in that the anode, cathode and solid electrolyte sheet are prepared according to the size requirements, all electrodes and electrolyte sheets are stacked and packaged in a laminated bag, the laminated bag is vacuum-treated, sealed, and the battery is pressurized at 490MPa by a static press. After pressing, the battery is taken out of the laminated bag, and the Al and Ni terminals of the cathode and anode are welded respectively using an ultrasonic welder, and the battery is placed in a laminated bag and vacuum-sealed again. Most of the assembly process is carried out in a dry air atmosphere, where the dew point is controlled below -50°C.

Citation Information

Cited By

  • Battery monomer, preparation method thereof, battery device and power utilization device

    CN122202481A